The Cretaceous-Tertiary boundary in the Iberian Peninsula marine record: meteoritic impact phases, diagenesis and paleoenvironmental effects deduced from rock magnetism - Villasante Marcos, Víctor; Martínez Ruiz, Francisca; Osete, María Luisa; Lamolda, Marcos A. (Física de la Tierra, 2010)
Detailed rock magnetic properties of four sedimentary marine sections spanning the Cretaceous- Tertiary boundary have been investigated in the Iberian Peninsula. In Agost and Caravaca (SE Spain), which present a very good preservation state of the impact ejecta layer that defines the boundary, the magnetic fingerprint of impact-generated Mg-Ni-rich spinels is revealed by increases of one order of magnitude in magnetic susceptibility and isothermal remanent magnetization (IRM), associated with a decrease in coercivity of remanence. This dominant ferrimagnetic phase is accompanied by a significant amount of high-coercivity antiferromagnetic material, mainly goethite with very fine grain sizes and haematite, resulting from early diagenesis under the anomalous post-impact conditions. Rock magnetism supports a post-impact increase in the terrigenous/carbonate ratio during the early Danian, followed by a recovery of carbonate production that exceeds the end-Maastrichtian values. Zumaya and Sopelana (N Spain) present worst preservation states of the impact ejecta layer. In Zumaya some patches of impact material are found on top of the calcite layer that separates the end-Maastrichtian from the K-T boundary clay. In these patches, increases in susceptibility and IRM and a decrease in coercivity of remanence point to the presence of Mg, Ni-rich spinels of meteoritic origin. In Sopelana, no vestiges of the impact ejecta layer were found, and consequently there is no magnetic evidence of meteoritic Mg-Ni-rich spinels; although the sampled interval is too narrow, magnetic properties point to a recovery of carbonate production in the early Danian exceeding that of the end-Maastrichtian, in agreement with Agost and Caravaca results.